Engineering and systems-level analysis of Saccharomyces cerevisiae for production of 3-hydroxypropionic acid via malonyl-CoA reductase-dependent pathway. Issue 1 (December 2016) - Kildegaard, Kanchana; Jensen, Niels; Schneider, Konstantin; Czarnotta, Eik; Özdemir, Emre; Klein, Tobias; Maury, Jérôme; Ebert, Birgitta; Christensen, Hanne; Chen, Yun; Kim, Il-Kwon; Herrgård, Markus; et al.
Abstract Background In the future, oil- and gas-derived polymers may be replaced with bio-based polymers, produced from renewable feedstocks using engineered cell factories. Acrylic acid and acrylic esters with an estimated world annual production of approximately 6 million tons by 2017 can be derived from 3-hydroxypropionic acid (3HP), which can be produced by microbial fermentation. For an economically viable process 3HP must be produced at high titer, rate and yield and preferably at low pH to minimize downstream processing costs. Results Here we describe the metabolic engineering of baker's yeastSaccharomyces cerevisiae for biosynthesis of 3HP via a malonyl-CoA reductase (MCR)-dependent pathway. Integration of multiple copies ofMCR fromChloroflexus aurantiacu s and of phosphorylation-deficient acetyl-CoA carboxylaseACC1 genes into the genome of yeast increased 3HP titer fivefold in comparison with single integration. Furthermore we optimized the supply of acetyl-CoA by overexpressing native pyruvate decarboxylasePDC1, aldehyde dehydrogenaseALD6, and acetyl-CoA synthase fromSalmonella enterica SEacs L641P . Finally we engineered the cofactor specificity of the glyceraldehyde-3-phosphate dehydrogenase to increase the intracellular production of NADPH at the expense of NADH and thus improve 3HP production and reduce formation of glycerol as by-product. The final strain produced 9.8 ± 0.4 g L−1 3HP with a yield of 13 % C-mol C-mol−1 glucose after 100 h in carbon-limited fed-batch cultivation at pH 5. The 3HP-producing strain was characterized by13 C metabolic flux analysis and by transcriptome analysis, which revealed some unexpected consequences of the undertaken metabolic engineering strategy, and based on this data, future metabolic engineering directions are proposed. Conclusions In this study, S. cerevisiae was engineered for high-level production of 3HP by increasing the copy numbers of biosynthetic genes and improving flux towards precursors and redox cofactors. This strain represents a good platform for further optimization of 3HP production and hence an important step towards potential commercial bio-based production of 3HP.